PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TAI DAN STRATEGI PQ4R PADA PEMBELAJARAN BIOLOGI KELAS X DI SMAN 1 TIGO NAGARI - Kurningsih, Titik; Haviz, M.; Rahmi, Elvy (Jurnal Pembelajaran MIPA, 2014)
The aim of this research is to find out the studentsâ achievement and activities by applying cooperative teaching of team assisted individualization (TAI) type and PQ4R strategy at the grade studentsâ of SMAN 1 Tigo Nagari. The design of this research is guasi experimental research by randomized control group post-test onlyÂ design. The procedurs of this research ensists of preparation, operation and post operation. The instruments of this research are test and observation sheet. The technique of data analysis used by the research was t-test. The result of the research shars that there is a significance differences of man score, standard denation, and variant among the control and experimental class. Therefore, it can be encluded that the studentsâ achievement of experimental class is better than the control class.Key words: cooperative teaching, type TAI and PQ4R Strategy, biology teaching